2019
DOI: 10.1177/1528083719893718
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the wear behavior and interlaminar shear properties of modified nano-TiO2/jute fiber/epoxy multiscale composites

Abstract: The main objective of the present work was to study the effects of nano-TiO2 on the dry-sliding wear properties and interlaminar shear strength of jute fiber/epoxy composite. The surface of TiO2 nanoparticles was functionalized by using a amin-terminated silane-coupling agent. Fourier-transform infrared spectroscopy and thermogravimetric analysis were used to characterize the modified TiO2 (M-TiO2). The multiscale composites were fabricated using hand layup technique by dispersing various amounts of the M-TiO2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
36
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 50 publications
(81 reference statements)
3
36
0
Order By: Relevance
“…When the nanofillers are not well dispersed in the matrix, local stress concentrations are created, leading to material failure at lower applied stresses. [34] It is noteworthy that, compared with GONPs, SiO 2 @GONPs is more effective for the increase of flexural properties of JF/EP composites. This may be mainly explained by the "barrier effect" mechanism.…”
Section: Characterizationmentioning
confidence: 97%
“…When the nanofillers are not well dispersed in the matrix, local stress concentrations are created, leading to material failure at lower applied stresses. [34] It is noteworthy that, compared with GONPs, SiO 2 @GONPs is more effective for the increase of flexural properties of JF/EP composites. This may be mainly explained by the "barrier effect" mechanism.…”
Section: Characterizationmentioning
confidence: 97%
“…Among the most nanoparticles, TiO 2 may be the most attractive on account of its properties, such as high chemical stability, super hydrophobicity, thermal stability, corrosion resistance, and great compatibility with various materials. [17,18] Furthermore, the relevant literatures have reported that TiO 2 nanoparticles have been successfully used in the epoxy, [19] polyethylene, [20] polypropylene, [21] and polybutylene succinate [22] to improve the mechanical performance. In addition, TiO 2 nanoparticles also have been used to improve tribological property of epoxy composites.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, TiO 2 nanoparticles also have been used to improve tribological property of epoxy composites. [19] Nanoparticles play a major role in improving the mechanical and fatigue resistance performances of epoxy through the nanoeffect, which is dependent on the dispersion states and distribution characteristics in the epoxy. How to obtain the homogeneous and cluster-free nanofillers in polymer matrix is the critical challenge, which can provide an enhancement effect for the epoxy under low filler content.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the last few decades, many methods have been used to improve the interfacial compatibility of plant fiber composites (eg, alkali treatment, 2 silane treatment, 23 acetylation, 24 plasma, 25 and nano‐TiO 2 26 ). Alkali treatment is one of the most effective and simple methods, after which the surface roughness of the plant fibers increases due to the removal of the partial lignin, wax, hemicellulose and the oil covering the fiber surface, increasing the interlocking force between the plant fiber and the polymer matrix 27 .…”
Section: Introductionmentioning
confidence: 99%